2003
DOI: 10.1287/inte.33.2.54.14473
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Abnormal Pricing in International Trade: The Greece-USA Case

Abstract: Government authorities, international lending agencies, and private sector firms try to detect abnormal pricing in international trade. Abnormal prices in international trade may indicate capital flight, import-duty fraud, income-tax evasion, or money laundering. We developed a framework for filtering all annual trades between two countries, which includes thousands of harmonized commodity codes and millions of import-export transactions. It produces a prioritized list of commodities traded at potentially abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…, which measures 1 Recent approaches and empirical studies use the price-comparison or unit-values approach, as suggested by Gabrisch and Szalai (2002), Pak et al (2003)…”
Section: Measuring Trade Misinvoicingmentioning
confidence: 99%
“…, which measures 1 Recent approaches and empirical studies use the price-comparison or unit-values approach, as suggested by Gabrisch and Szalai (2002), Pak et al (2003)…”
Section: Measuring Trade Misinvoicingmentioning
confidence: 99%
“…The price filter methodology espoused by Zdanowicz, Pak and Sullivan (1999) and by Pak, Zanakis and Zdanowicz (2003) is aimed at detecting international trade transactions that diverge from what is considered to be a normal price range (i.e. market price or freely competitive price) and then gauging the extent of that divergence.…”
Section: Overview Of Methodologies For Detecting Price Manipulatmentioning
confidence: 99%
“…More recently, the concern has been that false trade invoicing is being used as a source of money used to support terrorist activities. Empirical evidence of trade-based money laundering has been published in both academic and professional publications (Bhagwati, 1964;Cuddington, 1987;DeBoyrie et al, 2005b;De Wulf, 1981;Gulati, 1987;Pak et al, 2003;Zdanowicz et al, 1999;Zdanowicz, 2004b). …”
Section: Introductionmentioning
confidence: 99%